Routledge handbook of disability studies - Watson, Nick, 1960-; Roulstone, Alan, 1962-; Thomas, Carol, 1958- (New York : Routledge, 2012)
'The Routledge Handbook of Disability Studies takes a multidisciplinary approach to disability and provides an authoritative and up-to-date overview of the main issues in the field around the world today. Adopting an international perspective and consisting entirely of newly commissioned chapters arranged thematically, it surveys the state of the discipline, examining emerging and cutting edge areas as well as core areas of contention. Divided in five sections, this comprehensive handbook covers: Different models and approaches to disability ; How key impairment groups have engaged with disability studies and the writings within the discipline ; Policy and legislation responses to disability studies and to disability activism ; Disability studies and its interaction with other disciplines, such as history, philosophy and science and technology studies ; Disability studies and different life experiences, examining how disability and disability studies intersects with ethnicity, sexuality, gender, childhood and ageing. Containing chapters from an international selection of leading scholars, this authoritative handbook is an invaluable reference for all academics, researchers and more advanced students in disability studies and associated disciplines such as sociology, health studies and social work'--Provided by publisher.
Includes bibliographical references.
Keywords: Disability studies; People with disabilities; Disabled persons; Social values